Antecedents and Consequences of E-Learning Adoption in Jordanian Higher Education Institution - altawalbeh, manal (Advances in Social Sciences Research Journal, 2018)
This research aimed at investigating the factors influencing instructor’s intention to adopt e-learning by usingTechnology Acceptance Model in Jordanian universities. The paper takes a social and technical approach in its investigation by using a research theory based on Technology Acceptance Model (TAM) to identify the factors that affect intention to adopt e-learning. The sample consisted of (320) instructors. They were drawn randomly from the population, by using proportional stratified random sample method. A questionnaire was develop to collect data. Validity and reliability of the tool were assured. Multiple regression Analysis was used to assess the relationships in the constructs. The findings indicated that the perceived usefulness (PU) has a significant influence on behavioral intention (BI) (P<0.01), perceived usefulness (PU) and perceived ease of use (PEOU) have significant influence on Attitude (AT)( P<0.01),but attitude (AT) has no significant impact on behavioral intention BI (P>0.01).The study also provides an indicator of instructors’ acceptance of e-learning as well as identifying the important factors that would contribute to its successful use. The outcomes will enrich the understanding of instructor’s acceptance of e-learning and will assist in its continuing implementation at Jordanian Universities.